Agri-sustainability transitions: innovation-policy coordination mechanisms in green system restructuring - Yunxiao Yuan; Muhammad Umer; Xiaoyu Yang; Mei Qu (Frontiers in Sustainable Food Systems)
Achieving sustainable agricultural green development requires a dynamic and collaborative framework that integrates both innovation-driven mechanisms with policy guidance. This study employs an evolutionary game theory model to examine the interactions among farmers, government, enterprise, university research institutes, and social capital in the context of green farming practices. A multi-agent strategic decision model is developed to explore the stable conditions necessary for green agricultural cooperation and the factors influencing strategic equilibrium. The findings reveal that policy clarity and strength, market feedback on demand, intellectual property protection, and the collaborative capacity of innovation entities are all crucial for sustainable green farming practices. Moreover, the study highlights the negative impact of knowledge spillover, which can undermine cooperative efforts. Through analog simulation, the study demonstrates that targeted subsidies and regulatory mechanisms effectively promote the long-term sustainability of agriculture. These results offer policy insights for enhancing green development strategies through a balanced approach that combine internal innovation with external governance. The study contributes to the theoretical understanding of evolutionary game dynamics in green agricultural development and provides practical recommendations for policymakers, researchers, and enterprise stakeholders.